Pregnancy outcomes among female dental personnel - a registry-based retrospective cohort study - Ingrid Heggland; Ågot Irgens; Mette Tollånes; Pål Romundstad; Tore Syversen; Kristin Svendsen; Inger Melø; Bjørn Hilt (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: The aim of this study was to investigate whether women who have worked as dental personnel in Norway, a group with possible previous exposure to mercury vapor, have had an excess risk of having children with congenital malformations or other adverse pregnancy outcomes compared to the general population. METHODS: A cohort of female dental personnel was identified from the archives of the public dental healthcare and the national trade unions in Norway. Data on births and pregnancy outcomes during 1967-2006 were obtained from the Medical Birth Registry of Norway (MBRN). The final cohort of dental personnel consisted of 4482 dental assistants and 1011 dentists. All other women registered in the MBRN were assigned to the control group, in total 1 124 758. Excess risks of several adverse pregnancy outcomes for dental personnel compared to the general population were estimated. Analyses were conducted for the whole time period as well as stratified by 10-year periods. RESULTS: Female dental personnel had no observed increased occurrence of congenital malformations (including malformations of the central nervous system, dysplasia of the hip, clubfoot, malformations of the heart and great vessels), low birth weight, preterm birth, small for gestational age, changed gender ratio, multiple birth, stillbirth, or prenatal death. CONCLUSION: On a group level, we did not observe any excess risks of congenital malformations or other adverse pregnancy outcomes among female dental personnel in Norway during 1967-2006 compared to the general population